Examining the Contribution of Smart Homes to the Smart Performance of Cities - Daniel Orosz (Theory, Methodology, Practice, 2021)
One of the goals of smart cities is for their residents to live as comfortably as possible, at the highest possible standard of living, and for this, the existence of smart homes is essential. However, smart homes have so far not received much attention in smart city concepts, especially in Hungary. This study discusses definitions of smart cities and smart homes and asks how smart homes can contribute to increasing the performance of smart cities. I created a simplified model based on my search of the literature, which I supplemented with two new factors, which are emphasize the importance of people and education / communication.